1998
DOI: 10.1111/j.1600-0579.1998.tb00052.x
|View full text |Cite
|
Sign up to set email alerts
|

A study into the effectiveness of a text‐based computer‐assisted learning program in comparison with seminar teaching of orthodontics

Abstract: Computer-assisted learning (CAL) is a relatively new method of teaching. Few evaluations have been made which compare the new CAL methods with conventional teaching. This study used a text-based CAL package designed to teach orthodontic assessment and basic principles of treatment planning. It assessed the knowledge gain of 49 dental undergraduate students when taught orthodontic assessment and treatment planning by either CAL or conventional tutorial. Both groups made significant gains in knowledge. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
1
29
0
Order By: Relevance
“…The same authors reviewed EL in orthodontics and identified only four eligible studies (12). Two well designed ones were Clark et al (13) and Hobson et al (14). The first found no significant difference.…”
Section: Scientific Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors reviewed EL in orthodontics and identified only four eligible studies (12). Two well designed ones were Clark et al (13) and Hobson et al (14). The first found no significant difference.…”
Section: Scientific Backgroundmentioning
confidence: 99%
“…However, EL may not suit everybody particularly those with a less positive attitude towards it (14). This may stem from a lack of information communication technology (ICT) skills which is one of the main barriers to EL (25).…”
Section: Scientific Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…All disagreements were resolved by discussion. Fifteen of the articles were excluded, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] while twelve articles met the criteria for inclusion [28][29][30][31][32][33][34][35][36][37][38][39] in this review. Included articles featured CAL pro-grams in various dental disciplines: five in endodontics, three in orthodontics, one in oral anatomy, one in restorative dentistry, one in geriatric dentistry, and one in prosthodontics.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…There is much research comparing the effects of distance education with hands-on course education (HCE) that points out significant benefits of distance education along with its unwanted effects. 5 Taxonomies can be used to evaluate the perception level of education with various teaching methods. The Structure of the Observed Learning Outcomes (SOLO), which is often preferred for preparation of questions and evaluation of answers, was developed as a general cognitive development model by John Biggs and Kevin Collis.…”
Section: Introductionmentioning
confidence: 99%